Study on the Influence of Anasthesis Temperature and Time on Tiger Shrimp Survival Rate in Dry Transportation System - Rahman Karnila; Sam Herodian; Made Astawan; Rudy R Nitibaskara (Jurnal Keteknikan Pertanian, 1999)
The objective of this research is tojind out the best temperature, lime and handling method for black tiger shrimp transportation with dry system. Anesthesis method was applied in this research by adopting gradual cooling ut the rate of 5"Cper hour. Anesthesis was done at various temperatures ( I Y, 17, and 15°C) and time (10, 15, and 20 minutes) with temperature in puckuge 17°C. The result showed that the survival rate of black tiger shrimp was affrcted by anesthesis temperature, but not by the time of cooling at the criticaltemperature. The optimum temperature for anesthesis was 15°C with the optimum length of time was I0 minutes. Meanwhile the optimum temperature for transportation was 17°C. gave the highest survival of the black tiger shrimp (Penaeus monodon Fab.).Key words : Black Tiger Shrimp, Dry Transportation System